VERMIREMEDIATION – A REVOLUTION FOR SUSTAINING SOIL FERTILITY - BHARADWAJ, ALOK (International Journal of Psychosocial Rehabilitation, 2020)
Soil i.e. also called as mother land is a natural habitat, that play an important role in sustaining life because all living organisms whether plants, human, animals directly or indirectly depend on it for food and shelter. To meet the requirements of increasing human population, rapid industrialization, incorporation of chemical pesticides to increase the crop yield and other anthropogenic activities has polluted the soil. All such activities have increased the concentration of heavy metals, crude oil, petrol, diesel and other aromatic hydrocarbons in the soil upto the hazardous level. One of the remedial approach i.e. non toxic and environmental friendly is ‘vermiremediation’. In vermiremediation technology earthworms are used. They eat the soil contaminated with such toxic compounds, grind and digest them and excrete the dark coloured, porous, non hazardous material called vermicast. This vermicast have improved physicochemical properties and biological activity. Moreover, these earthworms also remediate toxic compounds like heavy metals, petroleum products within few weeks to months. Henceforth, vermiremediation is one of the potent tools for the remediation of toxic compounds in soil.